Intelligent high thermal conductivity copper-iron alloy with electromagnetic shielding function and preparation method thereof
By using a three-dimensional ordered Fe skeleton and nanoCu conduit structure in Cu-Fe alloy, combined with a copper oxide film, a [Cu/CuO/Fe] memristor network is formed, and the thermal conductivity and electromagnetic shielding performance of Cu-Fe alloy are compatible with each other. The problem of sexuality has achieved automated control and performance improvement.
Patent Information
- Application Number
- CN202310216388.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-08
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-03-08
AI Technical Summary
The existing Cu-Fe alloys are difficult to compatible with thermal conductivity and electromagnetic shielding performance, resulting in reduced conductivity and thermal conductivity or electromagnetic shielding performance loss, which cannot meet the needs of electronic devices for both heat dissipation and electromagnetic shielding.
Intelligent Cu-Fe alloy with three-dimensional ordered Fe skeleton and oriented arrangement of nanoCu catheters is used, and the Fe skeleton and nanoCu catheter are connected through copper oxide film to form a [Cu/CuO/Fe] memristor network to achieve electromagnetic shielding and automated control of thermal conductivity.
It achieves compatibility between thermal conductivity and electromagnetic shielding performance, and can automatically control the electromagnetic shielding and thermal conductivity of the alloy, improves the equipment's effectiveness for heat dissipation and electromagnetic field shielding, while reducing costs.
Smart Images

Figure CN116103536B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of heat conduction and electromagnetic shielding materials, and in particular relates to an intelligent high thermal conductivity copper-iron alloy (Cu-Fe Alloys) with electromagnetic shielding function and a preparation method thereof. Technical Background
[0002] With the continuous development of semiconductor and communication technology, the size of the internal devices of electronic communication equipment is getting smaller and smaller, and the stacking density is getting higher and higher, which directly leads to the increased sensitivity of electronic devices to heat sources and electromagnetic fields. In order to solve the problem of electronic devices being interfered by heat sources and electromagnetic fields, it is an ideal solution to introduce high thermal conductivity materials that can shield electromagnetic fields into the device. However, the heat dissipation module and electromagnetic field frequency blocking module inside general electronic equipment are independent of each other, occupying a large space in the equipment and having relatively simple functions, and it is impossible to realize the automatic control of heat dissipation and electromagnetic shielding performance. The development and design of materials that take into account both heat dissipation and electromagnetic shielding performance is an important prerequisite for the further development of electronic devices, and further requires such materials to be able to intelligently control their heat dissipation and shielding effectiveness.
[0003] Cu-Fe alloy is an electromagnetic shielding material that has attracted much attention at present. It has good electrical conductivity, thermal conductivity and electromagnetic shielding performance. At present, Cu-Fe alloy is usually prepared by smelting or powder metallurgy. The typical microstructure of the material is that micrometer or nanometer-sized Fe dendrite fragments are evenly dispersed in the Cu matrix. For example, the patent number is: CN201910530593.5, a high thermal conductivity copper-iron alloy material and its preparation method and application, using Cu powder and Fe powder as raw materials, melting into slurry in a vacuum induction furnace and then atomizing to make powder, and finally using electron beam drip melting process to melt the powder and cast to prepare Cu-Fe alloy material. During the solidification process, the alloy liquid phase is prone to liquid phase separation, forming a structure where Fe is segregated together, causing the electromagnetic shielding performance to be greatly affected by orientation, and at the same time, the electrical conductivity and thermal conductivity of the alloy are reduced; on the other hand, the Fe particles dissolved in the Cu matrix are poor conductors of heat, which is not conducive to the thermal conductivity of the Cu matrix, and will cause the electromagnetic shielding performance to be lost. The above problems make Cu-Fe alloy incompatible in terms of thermal conductivity and electromagnetic shielding performance. When Fe particles are segregated, the alloy's electrical and thermal conductivity are seriously lost, and some Fe particles are dissolved into the Cu matrix, which reduces the electromagnetic shielding performance, making it unusable in the heat dissipation module and electromagnetic field shielding module of electronic devices. Solving the compatibility problem of Cu-Fe alloy's thermal conductivity, electrical conductivity and electromagnetic shielding performance is an urgent need for the further development of current electronic communication equipment. Summary of the invention
[0004] In order to solve the compatibility problem between electromagnetic shielding performance and thermal conductivity of Cu-Fe materials and realize automatic control of electrical conductivity, thermal conductivity and shielding performance of alloys, the purpose of the present invention is to provide an intelligent thermal conductive alloy material with electromagnetic shielding function and a preparation method thereof. The internal microstructure of the intelligent Cu-Fe alloy is composed of a three-dimensional ordered Fe skeleton and three-dimensional directional arranged nano-conductor Cu conduits. The directional arranged nano-Cu conduits have high electrical conductivity and thermal conductivity and can meet the heat dissipation requirements of the equipment. The Fe skeleton can achieve electromagnetic field shielding by generating an induced magnetic field. The two are independent of each other to achieve compatibility between electromagnetic shielding and thermal conductivity. A layer of copper oxide (Cu O) film is interposed between the Fe skeleton and the nano-conductor Cu conduits, so that a [Fe / CuO / Cu] memristor network is established locally to achieve the purpose of controlling current and then controlling the magnetic field, thereby realizing automatic control of the electromagnetic shielding performance and electrical conductivity and thermal conductivity of the alloy.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The intelligent high thermal conductivity copper-iron alloy with electromagnetic shielding function includes a Fe skeleton network structure with spatial three-dimensional order, nano Cu conduits are directionally arranged around the Fe skeleton, and the Fe skeleton and the nano Cu conduits are connected by a nano CuO film.
[0007] The preparation method of the intelligent high thermal conductivity copper-iron alloy with electromagnetic shielding function comprises the following steps:
[0008] (1) First, Fe is prepared into a microscopic three-dimensional ordered network skeleton structure.
[0009] Cu is prepared into a nanotube structure with holes;
[0010] (2) Introduce a layer of CuO film around the inside of the Fe skeleton and etch it into a network array structure;
[0011] (3) The nano-Cu conduits are inserted into the Fe skeleton network structure in a directional manner and combined with the CuO film to form a [Cu / CuO / Fe] memristor array structure. The structure is then sintered at 300-600°C in a vacuum environment. The Fe phase in the prepared Cu-Fe alloy presents an orderly arranged skeleton structure, and the nano-Cu conduits are three-dimensionally arranged around the Fe skeleton. The formed [Cu / CuO / Fe] memristor has a two-dimensional network array structure, so that the current passing through the Cu conduits can be controlled by the memristor, thereby obtaining an intelligent high thermal conductivity copper-iron alloy with electromagnetic shielding function.
[0012] In the step (1), Fe is prepared into a microscopic three-dimensional ordered network skeleton structure, and the specific method is: using 3D printing, template method or injection molding process to prepare a Fe skeleton precursor with a predetermined ordered structure, and sintering the Fe skeleton precursor at 600-1000° C. in a vacuum or inert gas environment to prepare a controllable ordered Fe skeleton structure.
[0013] In the step (1), Cu is prepared into a nanotube structure with holes, and the specific method is as follows:
[0014] A nano-Cu conduit precursor with a predetermined porous structure is prepared using a 3D printing process. The nano-Cu conduit precursor is sintered at 400-600°C in a vacuum or inert gas environment to prepare a porous nano-Cu conduit structure with directional pore arrangement, and the pore size is consistent with the diameter of the nano-copper tube.
[0015] The specific implementation method of the step (2) is as follows: a layer of nano-CuO film is plated / deposited inside the Fe skeleton by magnetron sputtering, vacuum evaporation or physical vapor deposition technology, and then a two-dimensional planar CuO film array is formed inside the Fe skeleton by an oxide etching process.
[0016] Features of the present invention:
[0017] (1) The present invention changes the uniform distribution state of the Fe phase in the Cu-Fe alloy in the Cu matrix into a spatially ordered three-dimensional skeleton structure, uses porous nano-Cu conduits to surround the Fe skeleton, and connects the Fe skeleton and the nano-Cu conduits through a CuO film; this alloy modularizes the Fe phase and the Cu matrix so that they respectively assume the electromagnetic shielding function and the heat dissipation function, and can maximize the magnetic properties of the Fe phase and the thermal conductivity of the Cu matrix, thereby achieving high thermal conductivity and the compatibility of the electromagnetic shielding function and the thermal conductivity.
[0018] (2) The Cu-Fe alloy of the present invention has a [Cu / CuO / Fe] memristor array of size {m×n} (m, n≥2) inside, which can further realize automatic control of electromagnetic shielding performance and thermal conductivity and electrical conductivity by controlling the current state inside the alloy, thereby obtaining a high thermal conductivity copper-iron alloy material with electromagnetic shielding function; in addition, the number of memristor arrays in the present invention can be artificially controlled by changing the number of nano Cu conduits / the number of CuO film arrays, and the memristor array is formed in situ during the subsequent sintering process of the alloy, which can reduce costs while maintaining performance.
[0019] (3) The present invention transfers the resistance memory characteristics of the traditional [Cu / CuO / Fe] memristor to the Fe skeleton through the Faraday electromagnetic induction principle, so that it has the magnetic induction intensity memory characteristics, which is specifically manifested in that the [Cu / CuO / Fe] memristor array and the porous nano-Cu conduit in the present invention divide the Fe skeleton unit into (m×n) in space. 3 A magnetic domain unit is formed, each of which has a different magnetic domain orientation state under the influence of the [Cu / CuO / Fe] memristor, thereby realizing the magnetic induction intensity memory function. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of the internal structure of the high thermal conductivity copper-iron alloy with electromagnetic shielding function of the present invention.
[0021] Figure 2 It is a schematic diagram of the porous nano-Cu structure with directional hole distribution of the present invention.
[0022] Figure 3 It is a schematic diagram of the 3*3 nano CuO film array of the present invention.
[0023] Figure 4 It is a process diagram of the [Cu / CuO / Fe] memristor array of the present invention regulating electromagnetic shielding performance.
[0024] Specific method
[0025] The present invention is described in detail below with reference to the accompanying drawings and specific implementation examples.
[0026] See also Figure 1 , Figure 2 , Figure 3 The invention discloses an intelligent high thermal conductivity copper-iron alloy with electromagnetic shielding function, comprising a spatially ordered three-dimensional Fe skeleton network structure, nano-Cu conduits arranged around the Fe skeleton, and connecting the Fe skeleton and the nano-Cu conduits through a nano-CuO film. The internal structure of the invention is different from the typical microstructure of Fe phase particles dispersed in the Cu matrix in the traditional copper-iron alloy material. The microstructure of the invention is characterized by an ordered 3*3 array structure of Fe phase in the Cu-Fe alloy ( Figure 3 ), porous nano Cu conduit ring ( Figure 2 ) around the Fe skeleton and also presents a three-dimensional orderly arrangement in space, and the Fe skeleton and the nano Cu conduit are linked by the CuO film. This structure changes the basic structural characteristics of the internal heat conduction, electrical conduction phase and magnetic phase in the Cu-Fe alloy material in which the disordered random distribution is in place, so that the current and heat flow in the alloy are transformed from disordered flow to orderly directional flow, and the magnetic phase in the alloy can generate an induced magnetic field in situ when surrounded by the conductive phase, thereby shielding the external magnetic field electromagnetic field ( Figure 1), and at the same time, the high thermal conductivity nano-Cu conduit can quickly transfer the heat source to achieve the purpose of heat dissipation, thereby achieving the compatibility of high thermal conductivity and electromagnetic shielding functions, and its function is less affected by orientation and can be isotropic.
[0027] The present invention transfers the resistance memory characteristics of the traditional [Cu / CuO / Fe] memristor to the Fe skeleton through the Faraday electromagnetic induction principle to enable it to have magnetic induction intensity memory characteristics, which is specifically manifested in that the [Cu / CuO / Fe] memristor array and the porous nano-Cu conduit in the present invention divide the Fe skeleton unit into (m×n) in space. 3 A magnetic domain unit, each of which has a different magnetic domain orientation state under the influence of the [Cu / CuO / Fe] memristor, thereby realizing the magnetic induction intensity memory function, enabling the alloy to respond and feedback instantly to the current, and then realizing the magnetic property control of the magnetization phase, thereby realizing the automatic control of electromagnetic shielding and electrical and thermal conductivity. The specific control principle is carried out through the following steps, refer to Figure 4 :
[0028] S1: the high thermal conductivity copper-iron alloy with electromagnetic shielding function senses an external electromagnetic field Φ1;
[0029] S2: The copper-iron alloy has a spatially three-dimensional ordered Fe skeleton network inside, which is magnetized in response to an external electromagnetic field to generate an induced magnetic field Φ2 inside the alloy;
[0030] S3: The porous nano-Cu conduit with directional holes surrounding the Fe skeleton generates an induced circular current I under the influence of Faraday electromagnetic induction principle, and forms an excitation voltage U between the nano-Cu conduit and the Fe skeleton;
[0031] S4: The [Cu / CuO / Fe] memristor array is affected by the excitation voltage U and adjusts its own resistance R x , and then orderly regulate the circular current I in the nano Cu conduit;
[0032] S5: The induced magnetic field inside the Fe skeleton is affected by the circular current I in the nano Cu conduit to orderly regulate its own magnetic induction intensity, thereby completing the intelligent control of the electromagnetic shielding function.
[0033] Example 1
[0034] The intelligent high thermal conductivity copper-iron alloy with electromagnetic shielding function has a spatially three-dimensional ordered Fe skeleton network, nano-Cu heat pipes are directionally arranged around the Fe skeleton, and the Fe skeleton and the nano-Cu pipes are connected by a nano-CuO film.
[0035] Its preparation method is:
[0036] (1) First, an Fe skeleton precursor having a predetermined ordered structure is prepared, specifically: spherical nano-Fe powder with a particle size of 20-40 nm is uniformly mixed with 1-2 wt% of sodium dodecyl sulfate dispersant, and then 0.5 wt% of anhydrous ethanol (CH3CH2OH) is added and continued to mix, and after uniform mixing, the powder is dispersed by ultrasound and dried to obtain a nano-spherical Fe powder suitable for laser selective melting (SLM) technology, and the prepared powder is printed by SLM under program control to obtain a Fe skeleton precursor having a three-dimensional ordered structure, and then the printed Fe skeleton precursor is sintered at 600-800° C. in a vacuum environment to obtain a Fe skeleton preform having a three-dimensional ordered structure;
[0037] (2) Preparing a three-dimensional ordered Fe skeleton structure with a CuO thin film array on the inner surface: using vacuum evaporation technology, in an environment where argon (Ar) and oxygen (O2) are 15:1, a layer of CuO film with a thickness of 20-50 nm is deposited on the inner surface of the Fe skeleton preform with a three-dimensional ordered structure; then, an oxide etching technology is used to form a CuO film array on the inner surface of the Fe skeleton with a three-dimensional ordered structure. Figure 3 The CuO thin film array shown has an array size of 3×3 matrix, and finally a three-dimensional ordered Fe skeleton with a CuO thin film array on the inner surface is obtained;
[0038] (3) Spherical nano Cu powder with a particle size of 20-40 nm is mixed evenly with 1-2 wt% of sodium dodecyl sulfate dispersant, and then 0.5 wt% of anhydrous ethanol (CH3CH2OH) is added to continue mixing. After mixing evenly, it is dispersed by ultrasound and dried to obtain nano spherical Cu powder suitable for laser selective melting technology (SLM). The prepared powder is printed by SLM under program control to obtain a porous nano Cu conduit precursor with directional holes, and then the printed porous nano Cu conduit precursor is sintered at 400-600° C. in a vacuum environment to obtain the following Figure 2 The porous nano Cu conduit with directional holes as shown; (4) using micro-nano manufacturing and processing technology to prepare a copper-iron alloy material with a spatial three-dimensional ordered structure: placing the three-dimensional ordered Fe skeleton with a CuO thin film array in the center of a processing table in a vacuum environment, using a nanomanipulator to insert the porous nano Cu conduit with directional holes into the three-dimensional ordered Fe skeleton with a CuO thin film array to obtain a copper-iron alloy precursor with a spatial three-dimensional order, and then sintering the copper-iron alloy precursor with a spatial three-dimensional order at 300-500° C. in a vacuum environment to obtain Figure 1 The copper-iron alloy material shown has a spatial three-dimensional ordered structure.
[0039] Example 2
[0040] The intelligent high thermal conductivity copper-iron alloy with electromagnetic shielding function has a spatially three-dimensional ordered Fe skeleton network, nano-Cu heat pipes are directionally arranged around the Fe skeleton, and the Fe skeleton and the nano-Cu pipes are connected by a nano-CuO film.
[0041] Its preparation method is:
[0042] (1) First, an Fe precursor with a predetermined ordered structure is prepared, specifically: spherical iron powder with a particle size of 30-50 nm is ultrasonically dispersed in an anhydrous ethanol (CH3CH2OH) solution, and then dried to obtain spherical nano Fe powder with good dispersibility; mesoporous nano silica (SiO2) with a predetermined structure is used as a template, and its pore size is 60-100 nm, and the spherical nano Fe powder is used to fill the mesoporous nano SiO2 with a predetermined structure to prepare a Fe skeleton precursor with a predetermined three-dimensional ordered structure; the Fe skeleton precursor with a predetermined three-dimensional ordered structure is sintered at 800-1200° C. under a vacuum environment, and then immersed in hydrofluoric acid (HF) for 20-30 minutes to remove SiO2 in the Fe skeleton preform to obtain a Fe skeleton preform with a three-dimensional ordered structure;
[0043] (2) Preparing a three-dimensional ordered Fe skeleton structure with a CuO thin film array on the inner surface: Using magnetron sputtering technology, in an argon (Ar) environment, using CuO as a target material, depositing a CuO thin film array on the inner surface of the Fe skeleton preform with a three-dimensional ordered structure. Figure 3 The nano CuO film array shown has a thickness of 10-30 nm, and finally a three-dimensional ordered Fe skeleton with a CuO film array on the inner surface is obtained;
[0044] (3) Spherical nano Cu powder with a particle size of 20-40 nm is uniformly mixed with 1-2 wt% sodium dodecyl sulfate dispersant, and then 0.5 wt% anhydrous ethanol (CH3CH2OH) is added and continued to mix. After uniform mixing, it is dispersed by ultrasound and dried to obtain nano spherical Cu powder suitable for laser selective melting technology (SLM). The prepared powder is printed by SLM under program control to obtain a porous nano Cu conduit precursor with directional holes, and then the printed porous nano Cu conduit precursor is sintered at 400-600° C. in a vacuum environment to obtain the following Figure 2The porous nano Cu conduit with directional holes as shown; (4) using micro-nano manufacturing and processing technology to prepare a copper-iron alloy material with a spatial three-dimensional ordered structure: placing the three-dimensional ordered Fe skeleton with a CuO thin film array in the center of a processing table in a vacuum environment, using a nanomanipulator to insert the porous nano Cu conduit with directional holes into the three-dimensional ordered Fe skeleton with a CuO thin film array to obtain a copper-iron alloy precursor with a spatial three-dimensional order, and then sintering the copper-iron alloy precursor with a spatial three-dimensional order at 400-600° C. in a vacuum environment to obtain Figure 1 The copper-iron alloy material shown has a spatial three-dimensional ordered structure.
Claims
1. A method for preparing an intelligent high thermal conductivity copper-iron alloy with electromagnetic shielding function, characterized in that: The copper-iron alloy includes a spatially three-dimensional ordered Fe skeleton network structure, the nano Cu conduits are directionally arranged around the Fe skeleton, and the Fe skeleton and the nano Cu conduits are connected by a nano CuO film. The preparation steps are as follows: (1) First, Fe is prepared into a microscopic three-dimensional ordered network skeleton structure, and Cu is prepared into a nanotube structure with holes; (2) Introduce a layer of CuO film around the inside of the Fe skeleton and etch it into a network array structure; (3) The nano-Cu conduits are inserted into the Fe skeleton network structure in a directional manner and combined with the CuO film to form a [Cu / CuO / Fe] memristor array structure. The structure is then sintered at 300-600°C in a vacuum environment. The Fe phase in the prepared Cu-Fe alloy presents an orderly arranged skeleton structure, and the nano-Cu conduits are three-dimensionally arranged around the Fe skeleton. The formed [Cu / CuO / Fe] memristor has a two-dimensional network array structure, so that the current passing through the Cu conduits can be controlled by the memristor, thereby obtaining an intelligent high thermal conductivity copper-iron alloy with electromagnetic shielding function.
2. The method for preparing the intelligent high thermal conductivity copper-iron alloy with electromagnetic shielding function according to claim 1, characterized in that: In the step (1), Fe is prepared into a microscopic three-dimensional ordered network skeleton structure, and the specific method is: using 3D printing, template method or injection molding process to prepare a Fe skeleton precursor with a predetermined ordered structure, and sintering the Fe skeleton precursor at 600-1000° C. in a vacuum or inert gas environment to prepare a controllable ordered Fe skeleton structure.
3. The method for preparing the intelligent high thermal conductivity copper-iron alloy with electromagnetic shielding function according to claim 1, characterized in that: In the step (1), Cu is prepared into a nanotube structure having holes, and the specific method is as follows: A nano-Cu conduit precursor with a predetermined porous structure is prepared using a 3D printing process. The nano-Cu conduit precursor is sintered at 400-600°C in a vacuum or inert gas environment to prepare a porous nano-Cu conduit structure with directional pore arrangement, and the pore size is consistent with the diameter of the nano-copper tube.
4. The method for preparing the intelligent high thermal conductivity copper-iron alloy with electromagnetic shielding function according to claim 1, characterized in that: The specific implementation method of the step (2) is as follows: a layer of nano-CuO film is plated / deposited inside the Fe skeleton by magnetron sputtering, vacuum evaporation or physical vapor deposition technology, and then a two-dimensional planar CuO film array is formed inside the Fe skeleton by an oxide etching process.
Citation Information
Patent Citations
High-thermal-conductivity copper iron alloy material and preparation method and application thereof
CN110157944A
Preparation method for preparing copper-based electrical contact material according to 3D printing technique
CN109261961A
Copper-iron alloy, copper-iron alloy micro-nano composite porous material and preparation method of copper-iron alloy micro-nano composite porous material
CN111154997A